Neurovascular alterations of muscularis propria in the human anterior vaginal wall in pelvic organ prolapse. Issue 2 (30th May 2019) - Sferra, R; Pompili, S; D'Alfonso, A; Sabetta, G; Gaudio, E; Carta, G; Festuccia, C; Colapietro, A; Vetuschi, Antonella
Abstract: In the pathophysiology and progression of pelvic organ prolapse (POP), it has been demonstrated that there is a reorganisation of the muscularis propria of the anterior vaginal wall due to a phenotypic smooth muscle cell to myofibroblast switch. An abnormal deposition of collagen type III seems to be influenced by the involvement of advanced glycation end‐products. The aim of the present study was to evaluate the hypothesis that this connective tissue remodelling could also be associated with neurovascular alterations of the muscularis in women with POP compared with control patients. We examined 30 women with POP and 10 control patients treated for uterine fibromatosis. Immunohistochemical analysis, using glial fibrillary acidic protein, S‐100 protein, receptor tyrosine kinase, neurofilament and α‐smooth muscle actin antibodies, was performed. S‐100, receptor tyrosine kinase and neurofilament were also evaluated using Western blot analysis. We observed a decrease in all neurovascular‐tested markers in nerve bundles, ganglia and interstitial cells of Cajal from POP samples as compared with controls. Even if the processes responsible for these morphological alterations are still not known, it is conceivable that collagen III deposition in the anterior vaginal wall affects not only the architecture of the muscle layer but could also modify the intramuscular neurovascularisation and account for an alteration of the neuromuscular plasticity of the layer.